2005
DOI: 10.1111/j.1447-0756.2005.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Are vaginal fluid procalcitonin levels useful for the prediction of subclinial infection in patients with preterm premature rupture of membranes?

Abstract: These findings suggest that the value of vaginal fluid procalcitonin determinations is unsatisfactory in the diagnostics of pPROM cases suspected of subclinical intrauterine infection, as well as for the prediction of pPROM-to-delivery interval, newborn's congenital infection or histological chorioamnionitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…did not detect any association between cervicovaginal fluid ProCT levels and subclinical intra‐amniotic infection in PROM patients . However, they found higher cervicovaginal ProCT levels in PPROM patients than in term PROM patients and higher plasma ProCT levels in PPROM patients than in term PROM patients and healthy controls, which correlates with the results presented here. In the present study, we found higher ProCT levels in PPROM (group 1) patients than in PROM (group 2) patients and in healthy pregnant women at 24–36 weeks of pregnancy (group 3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…did not detect any association between cervicovaginal fluid ProCT levels and subclinical intra‐amniotic infection in PROM patients . However, they found higher cervicovaginal ProCT levels in PPROM patients than in term PROM patients and higher plasma ProCT levels in PPROM patients than in term PROM patients and healthy controls, which correlates with the results presented here. In the present study, we found higher ProCT levels in PPROM (group 1) patients than in PROM (group 2) patients and in healthy pregnant women at 24–36 weeks of pregnancy (group 3).…”
Section: Discussionsupporting
confidence: 88%
“…The CRP levels were measured by immunoturbidimetry using the Abbott Diagnostics Architect c16000 System (Abbott Diagnostics). The critical values for analysis of WBC and CRP were accepted as 15.0 c/mm 3 and 1 mg/dL, respectively, based on data from Torbe et al …”
Section: Methodsmentioning
confidence: 99%
“…Thornburg et al [30] concluded that the maternal serum procalcitonin level did not predict pathological CA, funisitis and neonatal sepsis. Also, Torbe and Czajka [31] did not find any correlation between cervicovaginal fluid procalcitonin levels and subclinical intraamniotic infection in PPROM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches were conducted to identify whether maternal CRP, procalcitonin and IL-6 can be used as noninvasive predictors of subclinical intraamniotic infection and EONS or not [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Kayem et al [23] reported that >20 mg/dl of CRP level predicted neonatal infection with 21% sensitivity, 95% specificity, 50% PPV and 84% NPV.…”
Section: Discussionmentioning
confidence: 99%
“…Some inflammatory mediators may also be detected in vaginal or cervical secretions, and it is probable that their concentrations in the vaginal compartment, especially after rupture of membranes, reflect their intraamniotic concentrations. 10,11 C-reactive protein (CRP) is an acute phase reactant produced by liver cells in response to interleukin-6 synthesized during infection, and it was proved that increased CRP values strongly indicate infectious complications. 12 Although maternal serum level of CRP slightly increases within gestational age, still this marker is used as an indicator of intrauterine infection, especially in pPROM cases [13][14][15][16][17][18] nevertheless reports that its benefits are conflicting.…”
Section: Introductionmentioning
confidence: 99%